Lethal encephalitis in a pediatric patient with SARS-CoV-2 - Yimenicioğlu, Sevgi; Zararcı, Kazım; Aynacı, Ali Murat; Yılmaz, Ayşe Tekin (The Turkish Journal of Pediatrics, 2022)
Background. SARS-CoV-2 mostly affects the respiratory system. Some studies have reported neurological disorders associated with SARS-CoV-2. Despite an increase in reported instances, encephalitis caused by COVID-19 infection is still poorly understood. Case. We reported a rare presentation of SARS-CoV-2 in a 15-year-old patient. He had a fulminant course with encephalitis. He had mild symptoms of a COVID-19 infection five months ago and recovered without any sequel. Despite appropriate treatment, the patient had a devastating course. Conclusions. This was a severe presentation of SARS-CoV-2 with central nervous system manifestations.
Keywords: SARS-CoV-2; childhood; encephalitis; status epilepticus